Exploring the Relationship Between Engineering Habits of Mind and Self-Regulation Skills in Children - Erol, Ahmet; Erol, Mustafa; Canbeldek, Merve (SPRINGER, 2026)
This study investigated the relationship between engineering habits of mind (EHoM) and self-regulation (SR) skills in 5- to 6-year-old children. The study employed a relational survey method and included 25 teachers and 400 children in their classrooms as participants. Data were collected using validated scales measuring engineering habits of mind and self-regulation skills and were analyzed using Pearson correlation analysis. The study's findings revealed a significant positive relationship between engineering habits of mind and self-regulation skills. Self-regulation components such as attentional flexibility, working memory, and inhibitory control are moderately positively related to systems thinking, optimism, creativity, collaboration, communication, and attention to ethical considerations, which are components of engineering habits of mind. Our findings contribute to the studies on self-regulation skills and engineering habits of mind, which are increasingly prevalent in early childhood.
Keywords: Engineering habits of mind; Self-regulation; Early childhood; PRESCHOOL CLASSROOM; THINKING; LITERACY; Education & Educational Research